2023
DOI: 10.48550/arxiv.2301.02396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Don't follow the leader: Independent thinkers create scientific innovation

Abstract: Academic success is distributed unequally; a few top scientists receive the bulk of attention, citations, and resources. However, do these "superstars" foster leadership in scientific innovation? We introduce three information-theoretic measures that quantify novelty, innovation, and impact from scholarly citation networks, and compare the scholarly output of scientists who are either not connected or strongly connected to superstar scientists. We find that while connected scientists do indeed publish more, ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Although academic impact is certainly a multifaceted concept, it is in fact undeniable that citations and citationbased indicators have become the currency of academic progression in a number of countries and academic systems [29], sometimes leading to unintended consequences on citation behaviours and patterns [18,30]. To push this analogy even further, a number of studies have shown that academic impact, as measured via citations, is partially inherited from mentors and/or senior collaborators [16,15,31,32], quite similarly to family wealth which is passed on through generations. We wish to stress that here we are not endorsing an uncritical use of citations and citation-based indicators as a measure of academic impact.…”
Section: Discussionmentioning
confidence: 99%
“…Although academic impact is certainly a multifaceted concept, it is in fact undeniable that citations and citationbased indicators have become the currency of academic progression in a number of countries and academic systems [29], sometimes leading to unintended consequences on citation behaviours and patterns [18,30]. To push this analogy even further, a number of studies have shown that academic impact, as measured via citations, is partially inherited from mentors and/or senior collaborators [16,15,31,32], quite similarly to family wealth which is passed on through generations. We wish to stress that here we are not endorsing an uncritical use of citations and citation-based indicators as a measure of academic impact.…”
Section: Discussionmentioning
confidence: 99%